Robust adaptive fuzzy controller for a class of non-affine nonlinear systems - Jie Wen; Changsheng Jiang; Li Zhou; Chengshan Qian (2008 2nd International Symposium on Systems and Control in Aerospace and Astronautics, 2008)
This paper present a direct adaptive fuzzy approach for a class of single-input-single-output (SISO) unknown non-affine nonlinear systems. A fuzzy logic system (FLS) is employed to approximate unknown plant nonlinearity. To update the adjustable parameters in FLS, a modified projection gradient algorithm is proposed which combines the advantage of projection gradient adaptive law and sigma - modification adaptive law. This algorithm is designed to ensure all signals involved are uniformly bounded and the track error is guaranteed to be uniformly asymptotically stable with the aid of an addition robust control term. Simulation results demonstrate the effectiveness and performance of the proposed approach.